Unlocking the Potential for Problem Solving Creativity through Transformational Leadership - Roellyanti, Maria Valeria; Lada, Suddin (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: This study analyzes the influence of personal characteristics (PC), creative work environment (CWE), cognitive skills (CS), and transformational leadership (TL), on creative problem solving (CPS) in the work environment.Design/methodology/Approach: Questionnaires were distributed for data collection. The questionnaire covers aspects including personal characteristics, cognitive skills, transformational leadership, creative work environment, and problem-solving creativity. This study involved 146 respondents from various tourism service industries. Regression analysis was used to test the relationship between independent, mediated, and dependent variables using structural equation Modeling (SEM).Research finding: The study shows that transformational leadership had a positive and significant influence on creative work environments. In addition, creative problem-solving is significantly influenced by the creative work environment and cognitive skills, although there is no significant influence between creative problem solving and personal characteristics.Theoretical Contribution/originality: The theoretical contributions of these findings reinforce the importance of transformational leadership in creating work environments that support creativity and strengthen the relationship between the creative work environment and creative problem-solving and cognitive skills. Practitioners Contribution/implications: Transformational leadership development through training and development is key for organizations to ensure leaders have the necessary skills to create creative work environments. Investment in creating work environments that support creativity involves the allocation of resources and efforts for workspace structuring and innovative policy development, along with efforts to enhance their capabilities in solving problems creatively.Research limitation/implications: The study's respondents were confined to one provincial area, specifically the Special Region of Yogyakarta. Expanding the study to multiple provinces would yield more comprehensive results.